2018
DOI: 10.1038/s41467-017-02513-0
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation orientations affect the evolution of a multicultural society

Abstract: The migration of people between different cultures has affected cultural change throughout history. To understand this process, cross-cultural psychologists have used the ‘acculturation’ framework, classifying ‘acculturation orientations’ along two dimensions: the willingness to interact with culturally different individuals, and the inclination to retain the own cultural identity (‘cultural conservatism’). Here, using a cultural evolution approach, we construct a dynamically explicit model of acculturation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…I follow previous cultural evolution researchers [ 16 , 17 ] in adapting population genetic methods and concepts to analyze cultural change, given that genetic and cultural change are both systems of inherited variation [ 18 ]. While past models have examined the effect of migration on cultural diversity [ 16 ] and the effect of acculturation in specific communities [ 19 ] and on multiculturalism [ 20 ], no past research has explicitly linked migration and acculturation to the maintenance of between-group cultural variation using quantitative measures of the latter. And while migration is often studied in sociology [ 21 ], psychology [ 15 ] and cultural anthropology [ 22 ], much of this work focuses on the proximate level (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…I follow previous cultural evolution researchers [ 16 , 17 ] in adapting population genetic methods and concepts to analyze cultural change, given that genetic and cultural change are both systems of inherited variation [ 18 ]. While past models have examined the effect of migration on cultural diversity [ 16 ] and the effect of acculturation in specific communities [ 19 ] and on multiculturalism [ 20 ], no past research has explicitly linked migration and acculturation to the maintenance of between-group cultural variation using quantitative measures of the latter. And while migration is often studied in sociology [ 21 ], psychology [ 15 ] and cultural anthropology [ 22 ], much of this work focuses on the proximate level (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the differences in breastfeeding beliefs and practices between those living in LMICs and HICs, there is evidence to show that immigrant mothers may or may not adopt practices of their host countries (Berry, ; Erten, van den Berg, & Weissing, ), despite the similarity of influential factors in both home and host countries (Gallegos et al, ; McFadden, Atkin, & Renfrew, ). A study conducted in Australia showed that African immigrant mothers maintained infant feeding practices from their countries of origin such as eating of special foods to aid milk production and enhance breastfeeding but also adopted some of the practices of the host country such as not breastfeeding in public places, which is contrary to practices in their home country (Gallegos et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, cultural factors influencing the nutrition status in high-income countries have changed substantially over time, with increasing immigration and inevitable transference of sociocultural norms across international boundaries (75) . This acculturation has resulted in a diversity in baseline health status and food selection practices of pregnant populations in high-income countries (76)(77)(78) . Hence, the nutritional needs of pregnant women in contemporary high-income regions differ considerably from those of the cohorts detailed by existing studies.…”
Section: Discussionmentioning
confidence: 99%